MANAGEMENT STRATEGIC FINANCIAL-INVESTMENT SUSTAINABILITY OF THE ENTERPRISE BASIS ON THE FORMATION OF THE MARKETING MECHANISM OF BEHAVIOR CONSUMERS (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In article is researched fundamental components of management strategic financial-investment sustainability of the enterprise. The analyzed theoretical approaches to the definition of the strategic sustainability of the enterprise in terms of financial and investment components and its combination with the formation of the marketing mechanism of consumer behavior. Identified prerequisites for the formation of strategic financial-investment sustainability on the basis of the competitiveness of enterprises, which determined by the complex management potential and consumer of behaviour. In addition, formed the main groups and the elements of the marketing mechanism of consumer behavior, which interpreted as a system management of strategic financial-investment sustainability of the enterprise simultaneous offering formula an effective model of strategic alternatives for its structure, which will include four main groups of functional dependencies and groups of factors, namely: strategy of commodity policy of the enterprise, strategys of the sales policy of the enterprise, strategys price policy of the enterprise, strategys communication policy of the enterprise with which will form the marketing mechanism of consumer behavior and implemented management of the strategic financial-investment sustainability of the enterprise
Keywords: management, strategy, marketing, financial-investment sustainability, market mechanism, behavior consumers